Enhancing motor skills and coordination in middle schoolers through innovative physical education programs - Andrada Maria BULZ; Mihai ȘANDRA; Anca Maria SABĂU; Emilia Florina GROSU; Gheorghe Codruț BULZ (GeoSport for Society)
New activities during physical education and sports classes attract children to the desire to exercise. This study, which involves two hours a week for a school year (8 months), in which children can experience new materials and learning tools during sports lessons, will improve their coordination and motor skills. The tests that the subjects of the experimental group will complete will bring coordination skills and the development of sensory perception. 3 of the tests used are for the development of kinesthetic sensitivity and 1 test will be for sensory-motor coordination. The results will show significant differences between the experimental and control groups after carrying out the program with the new work materials. In conclusion, the program carried out in the physical education and sports classes for two semesters led to significant improvements in terms of sensory-motor coordination and kinesthetic sensitivity of 10-14-year-old secondary school students.